Heterogeneity of electrically evoked dopamine release and reuptake in substantia nigra, ventral tegmental area, and striatum. - Cragg, S; Rice, M; Greenfield, SA (1997)
Somatodendritic dopamine (DA) released in substantia nigra pars compacta (SNc) and the ventral tegmental area (VTA) may mediate extrasynaptic neuronal signaling. The concentration of extracellular DA ([DA]o) attained during somatodendritic activation will be governed by the density of release sites and properties of DA uptake. We evaluated these factors in SNc, VTA, and dorsal striatum with carbon-fiber microelectrodes and fast-scan cyclic voltammetry to monitor [DA]o during local electrical stimulation (10 Hz, 5 s) in guinea pig brain slices. Stimulated DA efflux was site specific, with significantly higher [DA]o in caudal (0.48 +/- 0.03 microM, mean +/- SE) than rostral SNc (0.16 +/- 0.01 microM), averaged over their mediolateral extents, and higher [DA]o in VTA (0.74 +/- 0.07 microM) than in medial (0.43 +/- 0.04 microM) or lateral SNc (0.29 +/- 0.05 microM), averaged rostrocaudally. Throughout SNc, evoked [DA]o correlated positively (r = 0.91) with the density of tyrosine-hydroxylase-immunoreactive cells. Modulation of evoked [DA]o by uptake was also site specific. The selective DA uptake inhibitor GBR 12909 significantly increased evoked [DA]o in caudal SNc (to 185 +/- 27%) and striatum (408 +/- 24%), but had no effect in rostral SNc or VTA. Conversely, the norepinephrine (NE) uptake inhibitor desipramine did not alter stimulated [DA]o in caudal SNc or striatum, but caused significant enhancement in rostral SNc (196 +/- 17%) and VTA (126 +/- 12%). Paroxetine, a selective 5-hydroxytryptamine uptake inhibitor had little effect in any region tested. Site-specific sensitivity to desipramine mandated evaluation of dopamine-beta-hydroxylase immunoreactivity (D beta H-ir) in midbrain. The density of filaments positive for D beta H-ir was greater in rostral SNc and VTA than in caudal SNc, suggesting DA clearance via the NE transporter in these regions. Importantly, D beta H-ir was most dense in sections rostral to SNc where no catecholamine signal was detected and no enhancement was observed with desipramine, indicating a lack of NE contribution to evoked release in any region examined. Taken together, these data confirmed that evoked somatodendritic [DA]o depends on DA cell density and on local uptake properties. Uptake was less efficient in SNc and VTA than in striatum. Moreover, enhancement of stimulated [DA]o by GBR 12909 demonstrated that evoked release from dendrites is not via reversal of the DA transporter. Lastly, the heterogeneous patterns of DA uptake within SNc and VTA were consistent with the pattern of degeneration in Parkinson's disease; less vulnerable DA cells, e.g., those in VTA, have less DA uptake than the more vulnerable cells of caudal SNc.